Brain Abscesses Due to Aspergillus nidulans Infection During Induction Chemotherapy for Acute Lymphoblastic Leukemia. Issue 6 (August 2015) - Sadarangani, Manish; Harvey, Melissa; McDonald, Allison; Speert, David P.; Dix, David
Abstract : We present the case of a 3-year-old boy who was diagnosed with cerebral abscesses due to Aspergillus nidulans infection on day 28 of induction chemotherapy for acute lymphoblastic leukemia. He responded well to treatment with voriconazole and caspofungin, making a full recovery. There are very few cases of invasive aspergillosis reported in children during induction chemotherapy for acute leukemia and A. nidulans is rare in the absence of chronic granulomatous disease. Abstract : Supplemental Digital Content is available in the text.